Metabolic Reprogramming in HIV+ CD4+ T-Cells: Implications for Immune Dysfunction and Therapeutic Targets in M. tuberculosis Co-Infection - Suheena Ayrga; Gerrit Koorsen (Metabolites)
Background/Objectives: HIV and Mycobacterium tuberculosis (M.tb) co-infection presents a major global health burden. The immune response to M.tb is largely orchestrated by cluster of differentiation 4-positive (CD4+) T cells, with CD8+ T cells playing an auxiliary role. This study aims to investigate the immunometabolic response of CD4+ and CD8+ T cells to M.tb antigens, analysed using metabolomics, to elucidate metabolic shifts that may influence immune function in an HIV+ environment. Methods: Whole blood samples from newly diagnosed, treatment-naïve HIV+ individuals were stimulated with M.tb antigens early secreted antigenic target 6 (ESAT-6) and culture filtrate protein 10 (CFP-10) using the QuantiFERON® (QFT) Gold Plus assay. Following incubation, plasma samples were analysed through untargeted nuclear magnetic resonance (1H-NMR) spectroscopy. Metabolomic data were processed using MetaboAnalyst, with differential metabolites identified through multivariate statistical analyses. Results: Metabolic profiling of PBMCs revealed distinct differences in response to M.tb antigens between CD4+ and CD4+/CD8+ T-cell activation. CD4+ T cells exhibited enhanced glycolysis, with elevated levels of metabolites that are linked largely to the Warburg effect. Additionally, vitamin D levels were found to correlate with certain metabolites, suggesting a role in modulating immune responses. Conclusions: These findings suggest a complex interplay between immune cell metabolism and activation in HIV+ individuals. The study demonstrates that HIV and M.tb co-infection significantly influences the broader metabolic profile of peripheral blood mononuclear cells (PBMCs), highlighting the altered metabolic pathways that are critical in immune responses and disease progression. These findings contribute to the understanding of immunometabolism in co-infection and emphasise the need for further research into targeted metabolic interventions.